On vitamin D-dependent regulation of local mechanisms of non-specific defense in children with connective tissue dysplasia - L.I. Omelchenko; O.M. Mukvich; O.V. Lavrenchuk (Zaslavsky O.Yu., 2017)
Background. The influence of active vitamin D (VD) metabolites on the reaction of nonspecific defense mechanisms of mucous membranes may be of particular importance in children with connective tissue dysplasia (СТD). The purpose of the study was to establish the concentration of human -defensin (HBD-2) and lysozyme in local secretions in children with CTD taking into account the body's VD supply. Materials and methods. We examined 127 children aged 11-17 years with phenotypic manifestations of CTD taking into account the supplementation of VD. Four groups of children were identified: group 1 - healthy children with a physiological level of 25OHD, group 2 - children with moderate and severe CTD degrees and physiological concentrations of VD (75-100 nmol/l), group 3 - children with CTD and 25OHD insufficiency (50-75 nmol/l), group 4 - children with CTD and vitamin D deficiency (VDD) (below 50 nmol/l). Determination of HBD-2 level by immunoassay and lysozyme using a dry powder of one-day Micrococcus lyzodeiticus culture in local secretions (saliva, coprofiltrate (CF)) was performed in all children. Results. When studying HBD-2 in saliva, its highest concentrations were found in children of group 1 - 4.52 ± 0.06 ng/ml. Lower levels of HBD-2 were reported in children of groups 2 and 3, and in children with CTD and DVD, the rates were lowest - 3.88 ± 0.08 ng/ml. The highest HBD-2 concentrations in CF were detected in group 1 - 81.14 ± 5.13 ng/ml. In groups of children with dysplastic manifestations, a significant difference in data (p ≤ 0.05) is observed depending on the concentration of 25OHD, with the lowest concentrations found in VDD group - 52.63 ± 3.01 ng/ml. The highest lysozyme levels in CF were in children from groups 1 (4.68 ± 0.10 mg/l) and 2 (4.41 ± 0.09 mg/l); however, the lowest concentration of lysozyme was found in children with CTD and VDD - 4.09 ± 0.08 mg/l. A direct relationship is determined between the concentrations of vitamin D and lysozyme (r = 0.65). Conclusions. The obtained results indicated vitamin D-dependent regulation of the antimicrobial peptide production in the epitheliocytes of the intestinal mucosa in connective tissue dysplasia. The severity of HBD-2 and lysozyme production disorders in children with CTD and VDD determines the appropriateness of correcting vitamin D in this category of patients.